2019
DOI: 10.1148/ryct.2019180030
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided Core-Needle Biopsy of the Lung Is Safe and More Effective than Fine-Needle Aspiration Biopsy in Patients with Hematologic Malignancies

Abstract: To evaluate the safety and diagnostic yield of CT-guided core-needle biopsy (CNB) versus fine-needle aspiration biopsy (FNAB) of lung nodules and masses in patients with hematologic malignancies (HMs). Materials and Methods:With institutional review board approval, 166 patients were retrospectively reviewed between 2007 and 2017 who were diagnosed with leukemia, lymphoma, or myelodysplastic syndromes (with or without hematopoietic stem cell transplant) and who underwent CT-guided FNAB and/or CNB of the lung. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Although both fine-needle aspiration biopsies and core-needle biopsies can be used to diagnose mould infections, a consensus was achieved for transthoracic core-needle biopsies owing to their higher diagnostic yield ( figure 1 ). 58 , 59 , 60 , 61 The complication rates of transthoracic core-needle biopsies and fine-needle aspirates have been similar in the studies published before the COVID-19 pandemic. 58 , 59 , 60 , 61 , 62 However, considering the possibility of severe bleeding in patients with suspected CAPM, an alternative approach of performing a fine-needle aspiration cytology with on-site cytopathological examination might be considered before proceeding with core-needle biopsies.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Although both fine-needle aspiration biopsies and core-needle biopsies can be used to diagnose mould infections, a consensus was achieved for transthoracic core-needle biopsies owing to their higher diagnostic yield ( figure 1 ). 58 , 59 , 60 , 61 The complication rates of transthoracic core-needle biopsies and fine-needle aspirates have been similar in the studies published before the COVID-19 pandemic. 58 , 59 , 60 , 61 , 62 However, considering the possibility of severe bleeding in patients with suspected CAPM, an alternative approach of performing a fine-needle aspiration cytology with on-site cytopathological examination might be considered before proceeding with core-needle biopsies.…”
Section: Resultsmentioning
confidence: 66%
“… 58 , 59 , 60 , 61 The complication rates of transthoracic core-needle biopsies and fine-needle aspirates have been similar in the studies published before the COVID-19 pandemic. 58 , 59 , 60 , 61 , 62 However, considering the possibility of severe bleeding in patients with suspected CAPM, an alternative approach of performing a fine-needle aspiration cytology with on-site cytopathological examination might be considered before proceeding with core-needle biopsies.
Figure 1 Diagnostic algorithm for evaluating suspected CAPM CAPM=COVID-19-associated pulmonary mucormycosis.
…”
Section: Resultsmentioning
confidence: 66%
“…8,14 Our data did not show a correlation between CNB and an increased risk for bleeding which is comparable to similar studies in other organ sites, including liver and kidney. 23,24 ROSE plays an essential role in splenic FNA and CNB specimen triage for additional testing, leading to improved diagnostic rates. lymphoid aggregates containing cells in various stages of maturation with many isolated lymphoid cells in background.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of 166 patients with hematologic malignancy found bleeding complications more likely in those with a history of hematopoietic stem cell transplant. 18…”
Section: Relative Contraindicationsmentioning
confidence: 99%
“…Patients with hematologic malignancies are also considered high risk because of decreased or defective platelets, anemia, and immunosuppression. A retrospective review of 166 patients with hematologic malignancy found bleeding complications more likely in those with a history of hematopoietic stem cell transplant 18 …”
Section: Patient Factorsmentioning
confidence: 99%